2016
DOI: 10.1093/ejo/cjw063
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric covariation between palatal shape and skeletal pattern in children and adolescents: a cross-sectional study

Abstract: Covariation strength and pattern were similar in children and adolescents. The closer a subject was to the high-angle end of the variability spectrum, the higher and narrower was the palate, and conversely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 57 publications
3
32
0
Order By: Relevance
“…In subjects with skeletal Class II and retrusive mandible, males with hyperdivergent and normodivergent showed narrower in the posterior part of palate. These results were in agreement with Parcha's study, in which to explore the correlation between palatal morphology and skeletal pattern using GMM based on cephalograms and maxillary dental casts, and they reported skeletal Class II subjects with hyperdivergent pattern tended to have higher and narrower palate and emphasized that the most significant principal component related to palatal shape was vertical dimension [5].…”
Section: Comparison Of 3d Palatal Morphology With Different Vertical supporting
confidence: 90%
See 2 more Smart Citations
“…In subjects with skeletal Class II and retrusive mandible, males with hyperdivergent and normodivergent showed narrower in the posterior part of palate. These results were in agreement with Parcha's study, in which to explore the correlation between palatal morphology and skeletal pattern using GMM based on cephalograms and maxillary dental casts, and they reported skeletal Class II subjects with hyperdivergent pattern tended to have higher and narrower palate and emphasized that the most significant principal component related to palatal shape was vertical dimension [5].…”
Section: Comparison Of 3d Palatal Morphology With Different Vertical supporting
confidence: 90%
“…Previous studies with traditional methods to analyze cephalograms and observe dental casts focus on the influence of sagittal pattern on palatal morphology and suggested that skeletal Class II subjects was associated with narrow and high palatal morphology [1][2][3], especially those with retrusive mandible. However, literatures about the influence of vertical pattern on palatal morphology are insufficient and even controversial [4][5][6]. Three-dimensional (3D) methods to compare palatal morphology included either directly measuring palatal width, height, area and volume on conebeam computed tomography (CBCT) images or dental casts or obtaining 3D coordinates of palate, and then established two-dimensional (2D) mathematical models or superimposed on palate for comparison [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The palatal boundaries were assesed as: the midsagittal suture (9 points), the perimeter curve of the upper arch 5 passing apical to the gingival sulci of each tooth (21 points) and the posterior curve passing from distal of the first permanent molars, perpendicular to the midsagittal line (9 points). The other points (semilandmarks) were positioned uniformly on the maxillary surface within the confines delimited by the three curves 12,14,15 . The craniofacial skeletal shape was analysed through 15 continuous curves and 121 points (14 fixed cephalometric landmarks, 107 semilandmarks positioned at equidistant distances along the curves) 14,15 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The other points (semilandmarks) were positioned uniformly on the maxillary surface within the confines delimited by the three curves 12,14,15 . The craniofacial skeletal shape was analysed through 15 continuous curves and 121 points (14 fixed cephalometric landmarks, 107 semilandmarks positioned at equidistant distances along the curves) 14,15 (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%